1995
DOI: 10.2466/pms.1995.81.1.251
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Self-Efficacy and Dispositional Optimism on Adherence to Step Aerobic Exercise Classes

Abstract: This study investigated the effects of generalized and domain-specific expectancies on participation in 8 weeks of step aerobic-exercise classes. 154 university students and staff who registered for step aerobic classes completed measures of aerobic self-efficacy and dispositional optimism prior to attending their first class. Attendance was taken at each session by the instructors. A split at the median on attendance classified participants as dropouts or adherers. Analysis indicated that adheres scored signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
12
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 14 publications
4
12
1
1
Order By: Relevance
“…This agrees to previous research that has been done in the past where a positively high relationship was found between self-efficacy and continuity in exercise [28]. In comparison to these results, previous studies of the same nature also found a positive relationship between regular exercise and general self-efficacy [29,30]. Research has found that those who exercise and show continuity in exercise positively affects psychological phenomena like self-efficacy and psychological well-being, while not engaging in exercise or not considering exercise has a positive relation with depression [21].…”
Section: Discussionsupporting
confidence: 92%
“…This agrees to previous research that has been done in the past where a positively high relationship was found between self-efficacy and continuity in exercise [28]. In comparison to these results, previous studies of the same nature also found a positive relationship between regular exercise and general self-efficacy [29,30]. Research has found that those who exercise and show continuity in exercise positively affects psychological phenomena like self-efficacy and psychological well-being, while not engaging in exercise or not considering exercise has a positive relation with depression [21].…”
Section: Discussionsupporting
confidence: 92%
“…According to the findings, general self-efficacy and psychological well-being averages were high and depression levels were low when comparing those who exercise and those who do not. In comparison to these results, previous studies found a positive relationship between regular exercise and general self-efficacy (Fontaine & Shaw, 1995;Yeh et al, 2011). By examining literature on the relationship between regular physical activity and depression, being physically inactive in fact does have a positive effect on depression, which supports this study's findings (Camacho, Roberts, Lazarus, Kaplan, & Cohen, 1991;Paffenbarger, Lee & Leung, 1994;Strawbridge, Deleger, Roberts, & Kaplan, 2002).…”
Section: Discussionsupporting
confidence: 85%
“…Perceived self-efficacy has become an important and useful construct in psychology (2-4) because it is related to the willingness and the ability of people to engage in various behavioral challenges including preventive and disease management behaviors (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Studies in diabetes have demonstrated the effect of perceived self-efficacy on the adherence behavior of adolescents (16,17), African-American women with diabetes (18), adults with complex insulin regimens (18,19), and adults with type 1 or type 2 diabetes (20)(21)(22).…”
mentioning
confidence: 99%